Incorporation of Omega-3 Fatty Acids Into Human Skeletal Muscle Sarcolemmal and Mitochondrial Membranes Following 12 Weeks of Fish Oil Supplementation - Gerling, Christopher J.; Mukai, Kazutaka; Chabowski, Adrian; Heigenhauser, George J. F.; Holloway, Graham P.; Spriet, Lawrence L.; Jannas-Vela, Sebastian (Frontiers in Physiology, 2019)
Fish oil (FO) supplementation in humans results in the incorporation of omega-3 fatty acids (FAs) eicosapentaenoic acid (EPA; C20:5) and docosahexaenoic (DHA; C20:6) acid into skeletal muscle membranes. However, despite the importance of membrane composition in structure-function relationships, a paucity of information exists regarding how different muscle membranes/organelles respond to FO supplementation. Therefore, the purpose of the present study was to determine the effects 12 weeks of FO supplementation (3g EPA/2g DHA daily) on the phospholipid composition of sarcolemmal and mitochondrial fractions, as well as whole muscle responses, in healthy young males. FO supplementation increased the total phospholipid content in whole muscle (57%; p < 0.05) and the sarcolemma (38%; p = 0.05), but did not alter the content in mitochondria. The content of omega-3 FAs, EPA and DHA, were increased (+3-fold) in whole muscle, and mitochondrial membranes, and as a result the omega-6/omega-3 ratios were dramatically decreased (-3-fold), while conversely the unsaturation indexes were increased. Intriguingly, before supplementation the unsaturation index of sarcolemmal membranes was 3 times lower (p < 0.001) than either whole muscle or mitochondrial membranes. While supplementation also increased DHA within sarcolemmal membranes, EPA was not altered, and as a result the omega-6/omega-3 ratio and unsaturation index of these membranes were not altered. All together, these data revealed that mitochondrial and sarcolemmal membranes display unique phospholipid compositions and responses to FO supplementation.